Measurement of W W / W Z → ℓ ν q q ' production with the hadronically decaying boson reconstructed as one or two jets in pp collisions at s = 8 TeV with ATLAS, and constraints on anomalous gauge couplings - Aaboud, M; Aad, G; Abbott, B; Abdinov, O; Abeloos, B; Abidi, S H; AbouZeid, O S; Abraham, N L; Abramowicz, H; Abreu, H; Abreu, R; Abulaiti, Y; et al. (The European physical journal. C, Particles and fields, 2017)
This paper presents a study of the production of WW or WZ boson pairs, with one W boson decaying to e ν or μ ν and one W or Z boson decaying hadronically. The analysis uses 20.2 fb - 1 of s = 8 TeV pp collision data, collected by the ATLAS detector at the Large Hadron Collider. Cross-sections for WW / WZ production are measured in high- p T fiducial regions defined close to the experimental event selection. The cross-section is measured for the case where the hadronically decaying boson is reconstructed as two resolved jets, and the case where it is reconstructed as a single jet. The transverse momentum distribution of the hadronically decaying boson is used to search for new physics. Observations are consistent with the Standard Model predictions, and 95% confidence intervals are calculated for parameters describing anomalous triple gauge-boson couplings.